2020
DOI: 10.28940/terra.v38i1.564
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two remediation techniques applied to a site impacted by petroleum production waters

Abstract: Salinity in soils is a problem that has increased in recent years, in the Mexican southeast one of the main sources associated with these effects is the oil production water, affected congenital water. Although the chemical composition changes between one site and another, it is documented that its components can cause harmful effects on health and ecosystems. To recover the vocation to use recovery areas, different treatments have been established that eliminate standardized parameters, but others that may in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 41 publications
(46 reference statements)
2
11
0
2
Order By: Relevance
“…Generally, previous reports have established that most of the area is made up of associations of Vertisols and Gleysol (Palma-López et al, 2017), some of the results found in the control sample are in agreement with the properties of these kinds of associations and reports of Morales-Bautista et al (2017) and Gómez-Mellado et al (2020); specif ically, the values of T3 exposed in table 7, such as pH (moderately acidic), percentage of clay (> 50%), CEC in the range of 20 to 40 cmol + kg -1 (in relation to the content of %R and %MO, as exposed for Gutiérrez-Castorena andZavala, 2002 and, Álvarez-Coronel et al, 2020) and, add to the characteristics observed in the f ield, such as cracks and orange specks, high phreatic level and high reaction with H 2 O 2 in all horizons [that denotes the presence of organic matter in the whole prof ile (self-plowing) according to Sánchez-Hernández et al (2011) and Salgado-García et al (2016)]; in addition, Capdepont-Ballina and Marín-Olán (2014) reports that for similar soils with high demographics or anthropogenic activities, usually increases the %MO, which may coincide with the value of T3.…”
Section: Zonesupporting
confidence: 81%
See 2 more Smart Citations
“…Generally, previous reports have established that most of the area is made up of associations of Vertisols and Gleysol (Palma-López et al, 2017), some of the results found in the control sample are in agreement with the properties of these kinds of associations and reports of Morales-Bautista et al (2017) and Gómez-Mellado et al (2020); specif ically, the values of T3 exposed in table 7, such as pH (moderately acidic), percentage of clay (> 50%), CEC in the range of 20 to 40 cmol + kg -1 (in relation to the content of %R and %MO, as exposed for Gutiérrez-Castorena andZavala, 2002 and, Álvarez-Coronel et al, 2020) and, add to the characteristics observed in the f ield, such as cracks and orange specks, high phreatic level and high reaction with H 2 O 2 in all horizons [that denotes the presence of organic matter in the whole prof ile (self-plowing) according to Sánchez-Hernández et al (2011) and Salgado-García et al (2016)]; in addition, Capdepont-Ballina and Marín-Olán (2014) reports that for similar soils with high demographics or anthropogenic activities, usually increases the %MO, which may coincide with the value of T3.…”
Section: Zonesupporting
confidence: 81%
“…Moreover, it has been reported that the availability and abundance of nutrients, as well as the retention and degradation of pollutants, are directly related to the amount of organic matter and soil texture, for this reason some restoration works add material with these characteristics. For example, when organic material is added, what is sought is either to diminish the concentration of the contaminants to less toxic levels or their degradation to non-toxic reaction products (Gómez-Mellado et al, 2020;Kuppusamy et al, 2020). In other cases, the addition of inorganic and organic substances is intended to stabilize the contaminant by encapsulation or micellar sequestration (such as the pozzolanic reaction) and, subsequently, organic material with nutrients is added to return some properties to the soil to support planting (Adams et al, 2011;Álvarez-Coronel et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, Gómez-Mellado et al (2020) reported that the composition of the hydrocarbon could have changed due to a weathering process, because during that period several biotransformation, degradation and leaching processes took place. (2017) found that in old discharges, the residual fraction of hydrocarbons has low mobility and is difficult to degrade, but these compounds cause a reduction in water potential that is related to the reduction in crop production.…”
Section: Visual Soil Assessmentmentioning
confidence: 99%
“…Although, most of the norms consider a maximum concentration depending on the vocation of the soil, few of them include important parameters such as soil characteristics and changes in long-term pollutants (Kuppusamy et al, 2020). For example, hydrocarbons can interact with biotic and abiotic factors in the system so their chemical composition can change, especially when exposed to the environment for a long time (Gómez-Mellado et al, 2020). Adams et al (2016) and Vergeynst et al (2019) found that the soil type could influence the response to the pollutant since when evaluating areas with old spills.…”
Section: Introductionmentioning
confidence: 99%